2017
DOI: 10.1038/srep42099
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the temporal dynamics of suspended sediment during flood events with 7Be and 210Pbxs measurements in a drained lowland catchment

Abstract: Soil erosion is recognized as one of the main processes of land degradation in agricultural areas. High suspended sediment loads, often generated from eroding agricultural landscapes, are known to degrade downstream environments. Accordingly, there is a need to understand soil erosion dynamics during flood events. Suspended sediment was therefore sampled in the river network and at tile drain outlets during five flood events in a lowland drained catchment in France. Source and sediment fallout radionuclide con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
6
13
0
Order By: Relevance
“…Full details and assumptions are discussed in Matisoff et al (). This approach is not without drawbacks, as outlined in Le Gall et al () and Walling (). We use it in a limited and relative way and compute sediment age in order to evaluate the similarity between radionuclide activities and their ratios in precipitation and on suspended sediment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Full details and assumptions are discussed in Matisoff et al (). This approach is not without drawbacks, as outlined in Le Gall et al () and Walling (). We use it in a limited and relative way and compute sediment age in order to evaluate the similarity between radionuclide activities and their ratios in precipitation and on suspended sediment.…”
Section: Methodsmentioning
confidence: 99%
“…Scientists and resource managers are interested in the sediment fluxes on relatively short time scales, for example, storm events to seasons and years, often with an underlying motivation to know if a significant portion of sediment exported results from recent landscape surface erosion versus gully and streambank erosion (Bonniwell et al, ; Le Gall et al, ; Walling, ; Whiting et al, ). This requires an understanding of the sources and flow paths of both sediment and the water that erodes and carries it.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although suspended sediment yield was shown to globally decrease with slope (Milliman and Syvitski, 1992), small headwater lowland catchments may exhibit significant sediment exports (Vanmaercke et al, 2011). Previous studies investigated sediment transfer in these catchments by constructing sediment budgets (Walling and Collins, 2008) or conducting sediment fingerprinting (Smith and Blake, 2014; Foucher et al, 2015; Le Gall et al, 2017) approaches. Russell et al (2001) and Walling et al (2002) demonstrated the need to take into account tile drain networks in lowland catchments equipped with these systems.…”
mentioning
confidence: 99%